KEPUASAN REMAJA MENGGUNAKAN APLIKASI DISCORD (Studi Deskriptif Kuantitatif Kepuasan Remaja Menggunakan Aplikasi Discord di Surabaya) - Yulannugroho, Christian Hanggit (Universitas Negeri Surabaya, 2023)
Discord are one of the uses of new media to find information needs used by youth in Surabaya City. The purpose of this research is to find out how big the satisfaction level of Surabaya teenagers in using Discord. This study uses a quantitative approach, the population in this study is Surabayan youth who use Discord, with a sample of 96 respondents. The theory used in this study is the theory of Uses and Gratification, which in this study using 8 indicator in measuring the level of satisfaction, namely information satisfaction, personal identity satisfaction, integration and social interaction satisfaction, entertainment satisfaction, diversion satisfaction, personal relationship satisfaction, self identity satisfaction, and surveillance satisfaction. The results of this study show a comparison of the average (mean) score of each expected satisfaction (GS) and satisfaction obtained (GO), with a comparison of the average overall score of GS of 23.49 and GO's score of 30.77 (GS < GO) which means that the satisfaction obtained by Surabaya teenagers is greater than the expected satisfaction. This means that Discord have been able to meet the needs of the audience.